(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Treatment of advanced stage NSCLC has made many advances with a variety of treatment drugs. With low cost, high effectiveness and good tolerability, 1st generation Tyrosine Kinase inhibitors (TKIs) are the treatment option often chosen in the practice of treating stage IV NSCLC patients with EGFR gene mutations. The quality of life of stage IV lung cancer patients receiving targeted drug therapy is a crucial factor of concern to clinicians. However, in Vietnam, there are not many studies on the above issue. For the above reasons, we conducted this study to comment on the quality of life of stage IV lung cancer patients treated with generation I Tyrosine Kinase inhibitors. Subjects and methods: Prospective descriptive study on 51 stage IV UTP patients treated with I-generation TKI drugs at Internal Medicine Department 2, K Hospital from March 2023 to August 2024. Assessing quality of life using the EORTC C-30 and EORTC-LC13 questionnaires.Results: According to the EORTC C-30 questionnaire, changes in QOL in functional aspects after 1 month of treatment and 3 months after treatment had statistically significant improvements in most aspects (Physical activities, Social roles, Social integration, Psycho-emotion) except for the aspect of Cognitive ability. According to the EORTC-LC 13 questionnaire, symptoms of shortness of breath, cough, and pain improved after 1 month of targeted drug treatment and continued to improve after 3 months with p < 0.05. Symptoms of mouth pain, hair loss and peripheral neuropathy did not have statistically significant differences compared to before treatment. Conclusion: The first generation TKI treatment regimen brings about significant improvement in symptoms as well as overall improvement in QoL for patients with stage IV lung cancer.